Implementasi Pendidikan Karakter Dalam Meningkatkan Kedisiplinan Belajar Siswa di SD IT Al-Izzah Sibuhuan - Robiatul Adawiyah Pohan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The background of the research is the fact that there is a lot of moral decline that occurs in the younger generation of the Indonesian nation. This is evident in the world of national education that there are still many students who violate school regulations, ranging from not carrying out assignments, arriving late, missing school and student disobedience to their teachers. These various attitudes occur due to the depletion of the attitude of discipline and responsibility of students. The solution to this problem is the need for educational institutions that are able to overcome and build the character of learning discipline in students.The purpose of this study was to describe the implementation of character education in shaping student learning discipline at SD IT Al-Izzah Sibuhuan School. The research method uses a type of Qualitative research by taking location at SD IT Al-Izzah Sibuhuan. Interviews, observation and documentation are the data sources used in this research process. Qualitative descriptive analysis is the data analysis technique used. The results showed that the implementation of character education in shaping learning discipline at SD IT Al-Izzah Sibuhuan includes two aspects, namely implementation and school efforts. The implementation of character education implementation in shaping learning discipline through fun learning activities for students, habituation, discipline, infrastructure and fun learning. The school's efforts in implementing character education in shaping student learning discipline at SD IT Al-Izzah Sibuhuan are to create teaching and learning activities that are conducive, effective and fun. From the school, they also provide examples of student discipline to students so that they apply it to their daily activities to become better people.